Advances in magneto-ionic materials and perspectives for their application - M. Nichterwitz; S. Honnali; M. Kutuzau; S. Guo; J. Zehner; K. Nielsch; K. Leistner (APL Materials, 2021)
The possibility of tuning magnetic material properties by ionic means is exciting both for basic science and, especially in view of the excellent energy efficiency and room temperature operation, for potential applications. In this perspective, we shortly introduce the functionality of magneto-ionic materials and focus on important recent advances in this field. We present a comparative overview of state-of-the-art magneto-ionic materials considering the achieved magnetoelectric voltage coefficients for magnetization and coercivity and the demonstrated time scales for magneto-ionic switching. Furthermore, the application perspectives of magneto-ionic materials in data storage and computing, magnetic actuation, and sensing are evaluated. Finally, we propose potential research directions to push this field forward and tackle the challenges related to future applications.